Engineered octave frequency comb in integrated chalcogenide dual-ring microresonators - Wang, Zifu; Luo, Liyang; Xia, Di; Lu, Siqi; Lin, Guosheng; Gao, Shecheng; Li, Zhaohui; Zhang, Bin (Frontiers in Photonics, 2023)
Octave-spanning Kerr combs bridging the spectral windows of the near-infrared region (NIR) and the mid-infrared (MIR) region are expected in a number of applications, including high-capacity coherent optical communications, and gas molecular absorption footprints. Here, we propose novel concentric dual-ring microresonators (DRMs) for advanced dispersion engineering to tailor the comb spectral profile. The dispersion can be flexibly engineered not only by the cross-section of the DRMs, but also by the gap between concentric dual-ring microresonators, which provides a new path to geometrically control the spectral profile of the soliton Kerr combs. An octave-spanning Kerr soliton microcomb with multi-dispersive waves has been achieved numerically covering from the telecommunication band (1224 nm) to the mid-infrared band region (2913 nm) with a -40 dB bandwidth of 1265 nm. Our results are promising to fully understand the nonlinear dynamics in hybrid modes in DRMs, which helps control broadband comb formation.